Targeting the Nav1.6:GSK3β Protein:Protein Interaction Complex to Mitigate Hippocampal Hyperexcitability in Early‐Stage Alzheimer's Disease. (20th December 2022) - Baumgartner, Timothy J; Dvorak, Nolan M; Singh, Aditya K; Laezza, Fernanda; Group, Laezza Research
Abstract: Background: Nav1.6 is the most densely expressed sodium channel isoform in the adult brain and is a primary determinant of action potential initiation and propagation due to its subcellular localization at the axon initial segment (AIS). Importantly, it has been shown that the firing frequency and Na + currents of Nav 1.6 channels in hippocampal neurons are specifically increased by Aβ exposure in a concentration‐dependent manner. Nav1.6 is regulated through its interactions with key auxiliary proteins, notably Glycogen Synthase Kinase 3‐β (GSK3β), which has increased expression in the hippocampus of AD patients as well as peripheral circulating lymphocytes in both MCI and AD patients. We have shown that GSK3β regulates Nav1.6 channel activity through phosphorylation of and direct binding to the Nav1.6's intracellular C‐terminal domain (CTD). Furthermore, genetic silencing of GSK3Ββ significantly decreased both Na + currents and intrinsic firing compared to controls specifically through Nav1.6, while GSK3Ββ over‐expression or pharmacological disinhibition produced opposing phenotypes. Multiple lines of evidence indicate that hippocampal hyperactivity is present in patients with MCI and early‐stage AD and it is observed that reduction of hippocampal hyperactivity in MCI patients improves cognition and memory performance. We hypothesize that small‐molecule modulation of the Nav1.6:GSK3β PPI interface can counteract hippocampal hyperexcitability and could be used to treat early phases of AD, preventing the onset of cognitive decline. Method: HEK293 cells co‐transfected with WT or mutant Nav1.6 and GSK3β were utilized to interrogate the Nav1.6:GSK3β PPI and screen a series of 50 validated hit compounds using split‐luciferase complementation (LCA). Whole‐cell patch‐clamp electrophysiology was performed in heterologous cells and acute slice preparations to validate GSK3β‐mediated regulation of Nav1.6 activity and evaluate lead compound efficacy. Result: Mutagenesis screening revealed putative interaction sites of the Nav1.6:GSK3β PPI. Counter‐screening of 50 validated hits revealed 5 compounds that inhibit Nav1.6:GSK3β complex assembly at low micromolar concentrations (Figure 1). Compound 5671063, identified from the counter‐screen, exhibits functional modulation of Nav1.6 activity in heterologous cells (Figure 2). Conclusion: The Nav1.6:GSK3β complex is a critical mediator of neuronal activity and represents a novel target for treatment of pathological hippocampal hyperexcitability associated with cognitive decline.